Ambivalence of the person’s and culture’s Freudian concept of deviating behaviour’s context - L. S. Sysoyeva (Бюллетень сибирской медицины)
Freudian concept of deviating behaviour’s context is considered how duality in understanding of the person’s nature with primate of Lüstprinzip and Tanatos to social and cultural base brings about to certain justification of human behaviour’s deviations. And even disgruntles the culture. The Temptation of deviations is concluded in following. Than is call in question social explanation of deviating conduct.